KEPUASAN KERJA SEBAGAI MODERASI PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN - Ekaviana, Dessy; Kaluge, David (Jurnal Akun Nabelo : Jurnal Akuntansi Netral, Akuntabel, Objektif, 2019)
This research was conducted to determine the effect of Total Quality Management on Employee Performance with a moderating variable namely Job Satisfaction. The method used in this study is regression analysis. The conclusions from the results of data analysis are (1) Total Quality Management has a significant effect on Employee Performance so that by increasing the value of Total Quality Management (TQM) it will provide a significant increase in Employee Performance. (2) Total Quality Management and Job Satisfaction show insignificant influence on Employee Performance, so the hypothesis that Job Satisfaction moderates the relationship between Total Quality Management and Employee Performance is rejected because the effect is insignificant.